ANGLO-SOUTH AFRICAN RELATIONS AND THE EREBUS SCHEME, 1936-1939 - Visser, Deon (Scientia Militaria - South African Journal of Military Studies, 2011)
As a member of the Commonwealth, South Africa aligned its defence policy closely with that of Great Britain in the years between the two World Wars. Apart from taking responsibility for its own defence, the Union of South Africa was also expected, at its discretion, to support Britain in the case of a European war. By the mid-1930s South Africa faced a possible external threat as the aggressive, imperialist policies of Germany, Italy and Japan began to take shape. South African Defence Minister, Oswald Pirow, endeavoured to obtain 15-inch guns from Britain to bolster Cape Town’s defences against sea-raiders. Despite her strategic interest in safeguarding the Cape sea route, Britain’s own efforts at rearmament, however, made her unwilling to part with guns of that calibre. Instead, in June 1936, the British government agreed to lend the monitor HMS Erebus, carrying two 15-inch guns, to the Union of South Africa. Redesignated Erebus Heavy Battery, South African Garrison Artillery, it was to serve as a floating artillery battery in Cape Town harbour. Two detachments of South Africans were trained in Britain to man the Erebus, but war broke out before the Erebus could sail for the Cape. Some of the South African crew on the Erebus allegedly ‘refused duty’ and were put ashore. The Erebus scheme was subsequently cancelled and the South Africans sent home. The aim of this article is to determine the origins of the Erebus scheme and the reasons for its demise against the background of Anglo-South African relations immediately before and after the commencement of the Second World War. This entails an investigation of Anglo-South African relations both at interstate and popular level. The article outlines the birth of the scheme amidst the diverging views of the British Admiralty and the South African Minister for Defence, Oswald Pirow, on Cape Town’s defence needs. It highlights the political division in South African society over participation in a ‘British’ war on the eve of the Second World War and investigates the relationship between the South Africans and Britons on the Erebus. It concludes with a brief assessment of the role of the removal of some of the South African crew from the Erebus and the change of government in South Africa in the cancellation of the Erebus scheme.